Comprehensive return to competitive distance running: a clinical commentary - Hegedus, E. J.; Ickes, L.; Jakobs, F.; Ford, K. R.; Smoliga, J. M. (Sports Medicine, 2021)
Running injuries are very common, and there are well-established protocols for clinicians to manage specific musculoskeletal conditions in runners. However, competitive and elite runners may experience different injuries than the average recreational runner, due to differences in training load, biomechanics, and running experience. Additionally, injury-specific rehabilitation protocols do not consider the broader goal of return to competitive running, including the unique psychosocial and cardiorespiratory fitness needs of elite athletes. This review aims to suggest a guideline for running-specific progression as part of a comprehensive rehabilitation program for injured competitive runners. Tools to evaluate an athlete`s psychosocial preparedness to return to competition are presented. Recommendations are also provided for monitoring cardiorespiratory fitness of injured runners, including the nuances of interpreting these data. Finally, a six-phase training paradigm is proposed to guide clinicians as they help competitive runners transition from the early stages of injury through a full return to competition.